2015
DOI: 10.1007/s13594-015-0272-z
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and antibiotic resistance of enterotoxigenic Staphylococcus aureus in raw ovine and caprine milk in Greece

Abstract: Ovine (n=140) and caprine (n=35) raw bulk tank milk samples from farms in central Greece were examined for the occurrence of enterotoxigenic Staphylococcus aureus. The S. aureus isolates were screened for staphylococcal enterotoxin (SE) production, the presence of enterotoxin genes, antibiotic resistance (AR), and methicillin resistance. S. aureus was isolated from 24.3% and 31.4% of ovine and caprine milk samples, respectively. Among the S. aureus isolates of ovine milk (n=34) and caprine (n=11) milk, the ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
21
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 45 publications
6
21
3
Order By: Relevance
“…Despite this high overall S. aureus prevalence, the estimated MRSA prevalence was low (0.7%; 2/286). This finding is in agreement with those of other recent investigations carried out on small ruminant BTM in Italy (Caruso et al, 2015;Cortimiglia et al, 2015), Spain (Ariza-Miguel et al, 2014), and Greece (Pexara et al, 2015;Zdragas et al, 2015), which reported prevalence rates ranging from 0 to 2%.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Despite this high overall S. aureus prevalence, the estimated MRSA prevalence was low (0.7%; 2/286). This finding is in agreement with those of other recent investigations carried out on small ruminant BTM in Italy (Caruso et al, 2015;Cortimiglia et al, 2015), Spain (Ariza-Miguel et al, 2014), and Greece (Pexara et al, 2015;Zdragas et al, 2015), which reported prevalence rates ranging from 0 to 2%.…”
Section: Discussionsupporting
confidence: 93%
“…As for the antimicrobial susceptibility testing of the MSSA isolates, we found that 60.58% of them were susceptible to all the drugs tested. Lower rates of antimicrobial resistance have been reported in other studies conducted in Greece (Pexara et al, 2015;Zdragas et al, 2015) and Brazil (Martins et al, 2015). The most common resistance was that to tetracycline, observed in 22.12% of the isolates, a rate higher than that described in other studies in Italy (Lollai et al, 2008), Turkey (Ünal et al, 2012, and Brazil (Martins et al, 2015), but lower than that reported in Iran by Jamali et al (2015).…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…() found the presence of the seb gene in one isolate only and they reported that all other genes ( sea , sec , sed , and see ) were not detected in any isolate. Several studies described that none of the investigated isolates from bovine and goat milk and dairy products harbored the gene seb (Akineden et al., ; Lyra et al., ; Pexara, Solomakos, Sergelidis, Angelidis, & Govaris, ). In other studies, however, the seb gene was detected in S. aureus isolates from milk and dairy products at various frequencies (Arcuri et al., ; Jorgensen et al., ; Peles et al., ; Rall et al., ; Zouharova & Rysanek, ).…”
Section: Resultsmentioning
confidence: 99%